Gene-environment interaction between body mass index and transforming growth factor beta 1 (TGFβ1) gene in knee and hip osteoarthritis - Muthuri, Stella G.; Doherty, Sally; Zhang, Weiya; Maciewicz, Rose A.; Muir, Kenneth R.; Doherty, Michael (BioMed Central, 2013)
Introduction: The objective was to investigate potential gene-environment interaction between body mass index (BMI) and each of eight TGFβ1 polymorphisms in knee and hip osteoarthritis (OA). Methods: We conducted a case-control study of Caucasian men and women aged 45 to 86 years from Nottingham, United Kingdom (Genetics of OA and Lifestyle (GOAL) study). Cases had clinically severe symptoms and radiographic knee or hip OA; controls had no symptoms and no radiographic knee/hip OA. We used logistic regression to investigate the association of TGFβ1 polymorphisms and OA when stratifying by BMI. Knee and hip OA were analyzed separately with adjustment for potential confounders. Additive and multiplicative interactions were examined. Results: 2,048 cases (1,042 knee OA, 1,006 hip OA) and 967 controls were studied. For hip OA, the highest risk was in overweight (BMI ≥25 kg/m2) individuals with the variant allele of single-nucleotide polymorphism (SNP) rs1800468 (odds ratio (OR) 2.21, 95% confidence interval (CI) 1.55, 3.15). Evaluation of gene-environment interaction indicated significant synergetic interaction (relative excess risk due to interaction (RERI) = 0.93, synergy index (SI) = 4.33) with an attributable proportion due to interaction (AP) of 42% (AP = 0.42; 95% CI 0.16, 0.68). Multiplicative interaction was also significant (OR for interaction (ORINT) = 2.27, P = 0.015). For knee OA, the highest risk was in overweight individuals with homozygous genotype 11 of SNP rs2278422 (OR = 6.95, P < 0.001). In contrast, the variant allele indicated slightly lower risks (OR = 4.72, P < 0.001), a significant antagonistic interaction (RERI = -2.66, SI = 0.59), AP = -0.56 (95%CI -0.94, -0.17) and a significant multiplicative interaction (ORINT = 0.47, P = 0.013). Conclusion: TGFβ1 gene polymorphisms interact with being overweight to influence the risk of large joint OA.